Effects of various elicitors on the accumulation and secretion of spiroketal enol ether diacetylenes in feverfew hairy root culture - Anna Stojakowska; Jan Burczyk; Teresa Duda; Wanda Kisiel; Anna Banaś; Maria Zych (Acta Societatis Botanicorum Poloniae, 2011)
In a hairy root culture of Tanacetum parthenium treated with yeast extract (YE), silver nitrate (AgNO3) and microalgal glycoproteins (MGPS), contents of four spiroketal enol ether type diacetylenes were mesured. The elicitors transiently reduced contents of three constitutive spiroketal enol ethers and selectively enhanced accumulation of cis-C13-spiroketal enol ether epoxide ((E)-3,4-epoxy-2-(2,4-hexadiynylidene)-1,6-dioxaspiro[4.4]nonane) in the roots. The most abundant formation of cis-C13-spiroketal enol ether epoxide was observed after 48-96 h of AgNO3 treatment and 96 h of YE treatment (over 3-fold increase compared with the control). The applied elicitors caused enhanced liberation of cis-C13-spiroketal enol ether epoxide to the culture medium. The results show that diacetylene accumulation pattern in the elicited hairy roots is affected in a similar manner, irrespectively of the elicitor applied.